PENGARUH PSYCHOLOGICAL EMPOWERMENT TERHADAP JOB PERFORMANCE DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL MEDIASI - Mahendra, Angga Tri Ananda; Zona, Mega Asri (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
Purpose: This research reveals: (1) impact of psychological empowerment in job performance (2) effect of psychological empowerment on organizational citizenship behavior (3) effect of organizational citizenship behavior on job performance (4) effect of psychological empowerment on job performance through organizational citizenship behavior, Methods:  This research is a causal research. The population of this study were partnership employees of PT Pos Indonesia Main Branch Office Padang City. The amount of samples used are population of 40 partnership employees. This data collecting by using questionnaire with a Likert Scale. The technique of analysis used is through SmartPLS 4 software. Result and discussions: The results of  this research explain that: (1) psychological empowerment have good and important impact to job performance in partnership employees of PT Pos Indonesia Main Branch Office Padang City (2) psychological empowerment have good and important impact on organizational citizenship behavior in partnership employees of PT Pos Indonesia Main Branch Office Padang City (3) organizational citizenship behavior has a good and important effect on job performance in partnership employees of PT Pos Indonesia Main Branch Office Padang City (4) psychological empowerment has good and impotant effect on job performance through organizational citizenship behavior in partnership employees of PT Pos Indonesia, Padang Main Branch Office.